Development of Astronium fraxinifolium Schott seedlings: A native tree from Cerrado - Cristina Marques Leite, Marilaine [UNESP]; Souza Leal, Alice [UNESP]; Cagnin Pereira, Thalissa [UNESP]; Redondo Martins, Aline [UNESP] (Elsevier, 2022)
Plant ontogeny studies can identify anatomical and morphological functional traits which enable species survival under different edaphoclimatic conditions. Ontogenetic studies can also help in recovering degraded areas projects. Astronium fraxinifolium (Anacardiaceae), a Cerrado tree, is a deciduous, heliophyte, pioneer and widely used in reforestation and recovery of degraded areas. The aim of this study was to describe the vegetative morphoanatomical development of A. fraxinifolium seedlings during the first year after seed germination, as well as to identify traits that enable their germination, establishment and growth for their use in reforestation and ecological studies of Cerrado areas. Seedlings of different ages of A. fraxinifolium were produced in a greenhouse. The plants were fixed, dehydrated, embedded in synthetic resin, and sectioned on a microtome for subsequent anatomical analysis. Hypogeal germination was observed and a germination rate of 96.1%. The species also had rapid growth, with secondary growth observed in the stem and root already at six months of development. The species had starch stored in the stem and root, which enables their survival under environmental disturbance. Additionally, this species had numerous secretory ducts filled with phenolic compounds in all organs, which can protect against predation.
Keywords: Functional traits; Germination; Ontogeny; Seedling development